Synthesis of two new arsenolipids and their identification in fish. Issue 3 (2nd June 2015) - Arroyo‐Abad, Uriel; Hu, Zehan; Findeisen, Matthias; Pfeifer, Dietmar; Mattusch, Jürgen; Reemtsma, Thorsten; Piechotta, Christian
Abstract : Arsenolipids (AsL) of the type arsenic‐containing fatty acids (AsFA) and hydrocarbons (AsHC) are natural organoarsenic compounds present in high abundance in seafood. Since little is known about their toxicity, there is a significant concern about their health risk. Here we report the synthesis of two new AsL and their identification in fish by liquid chromatography (LC) coupled simultaneously to inductively coupled plasma mass spectrometry (ICP‐MS) and to high resolution mass spectrometry (HR‐MS). The molecular structure was elucidated on the basis of their exact mass and their product ion mass spectra. One of the synthesized AsL has been already identified in fish samples, meanwhile, the other arsenolipid is reported here as a natural product in fish. Practical applications: The synthesized AsL can be used as analytical standards to confirm the identification of AsL in different biological samples and to optimize analytical methods for their determination by liquid chromatography coupled simultaneously to ICP‐MS and HR‐MS. The material can be further used for toxicity testing of AsL and to study their uptake, bioavailability, and biotransformation. We report the synthesis of two new arsenolipids and their identification in fish by liquid chromatography (LC) coupled simultaneously to inductively coupled plasma mass spectrometry (ICP‐MS) and to high resolution mass spectrometry (HR‐MS). One of the synthesized arsenolipid has been already identified in fish samples, meanwhile, the other arsenolipid is reported for the first time here as a natural product in fish. Abstract : We report the synthesis of two new arsenolipids and their identification in fish by liquid chromatography (LC) coupled simultaneously to inductively coupled plasma mass spectrometry (ICP‐MS) and to high resolution mass spectrometry (HR‐MS). One of the synthesized arsenolipid has been already identified in fish samples, meanwhile, the other arsenolipid is reported for the first time here as a natural product in fish.